Nanomechanical detection to empower robust monitoring of sepsis and microbial adaptive immune system-mediated proinflammatory disease - Kessarin Thanapirom; Walid Al-Akkad; Aylin Pelut; Zahra Sadouki; Jemima B. Finkel; Stefan Nardi-Hiebl; Wieland Vogt; Benjamin Vojnar; Hinnerk Wulf; Leopold Eberhart; Timothy D McHugh; Krista Rombouts; et al. (Scientific Reports)
Abstract The correlation between circulating microbes and sepsis as well as proinflammatory diseases is increasingly gaining recognition. However, the detection of microbes’ cell-free DNA (cfDNA), which exist at concentrations of a billion times lower than blood proteins, poses a significant challenge for early disease detection. Here, we present Nano mechanics combined with highly sensitive readout sequences to address the challenges of ultralow counts of disease biomarkers, thus enabling robust quantitative monitoring of chronic medical conditions at different stages of human disease progression. To showcase the effectiveness of our approach, we employ fragments of cfDNA and human cell secretory proteins as models with predictive capabilities for human diseases. Notably, our method reveals a reliable representation over an impressive three to four orders of magnitude in the detection limit and dynamic range, surpassing commercially available quantitative polymerase chain reaction (qPCR) commonly used in routine clinical practice. This concept underpins a highly sensitive and selective medical device designed for the early detection of circulating microbes in patients undergoing intensive cancer therapy. This will help pinpoint individuals at risk of complications, including damage to the intestinal barrier and development of neutropenic fever/Sirsa/Sepsis. Moreover, this approach introduces new avenues for stratifying antibiotic prophylaxis in proinflammatory diseases.